"Acceptable" Cartels at the Crossroads of EU Competition Law and the Common Agricultural Policy: A Legal Inquiry into the Political, Economic, and Social Dimensions of (Strengthening Farmers') Bargaining Power. (September 2020) - Cseres, K. J.
Why does the European Union (EU) law allow for special treatment of the agricultural sector? Which exceptions exist in applying the EU competition rules in this sphere, and how has their interpretation evolved? How do these derogations address the fragmented nature of the agricultural sector and strengthen farmers' bargaining powers, and what are the justifications for doing so? These are the questions that the current article seeks to answer, by analyzing the specific constitutional constellation of the EU's agricultural policy alongside its competition rules. This article critically analyzes how derogations in the field of agriculture have developed in a market-oriented way, yet an unresolved tension remains with the objectives of the Treaty's competition rules. This article revisits this tension and its underlying legal framework by taking account of the risk of political capture as well as of relevant socioenvironmental externalities, most notably environmental and social sustainability, which could shape its transformation in the future.